New insights towards the establishment of phycocyanin concentration thresholds considering species-specific variability of bloom-forming cyanobacteria - Macário, Inês P. E.
In vivo phycocyanin (PC) fluorescence allows assessing cyanobacterial abundance in an easy, fast and cost-effective way. However, the establishment of PC thresholds is necessary for its use in routine monitoring programmes and there has been no consensus regarding their definition. This work aimed: (1) to assess the potential species-specific variation in fluorometric PC content among Microcystis aeruginosa, Nostoc muscorum and Cylindrospermopsis raciborskii; (2) to propose specific PC thresholds based on World Health Organization alert levels; and (3) to evaluate the in vivo PC signal reliability to interferences from massive algal growth and mixtures of bloom-forming cyanobacteria. Strong linear relationships were recorded between PC and cell counts, biovolume and chlorophyll a. However, a significant species-specific variation in PC was observed using cell counts. Increased microalgal densities did not cause significant interference of PC signals. Also, dual mixtures of cyanobacteria revealed strong relationships between measured and expected PC content. Results suggest that fluorometric PC is a good predictor for cyanobacterial biomass but cell number is not the best parameter to define thresholds. Biovolume should be used instead. Nevertheless, speciesspecific thresholds must be considered, rather than a general cyanobacterial threshold.